EFEKTIVITAS KOMBINASI SENAM OTAK DAN ALAT PERMAINAN EDUKATIF MAZE PAPAN ALUR TERHADAP PENINGKATAN MOTORIK HALUS PADA ANAK TAMAN KANAK-KANAK AISYIYAH BUSTANUL ATHFAL RANTING MALIMONGAN TUA KOTA MAKASSAR - Arpandjaman Arpandjaman; Suharto Suharto; Afifah Nur; Sudaryanto Sudaryanto (Politeknik Kesehatan Makassar, 2021)
Background: Preschool age is a golden age for the child's development process where at that age the cognitive, physical, motor and psychosocial aspects of a child develop optimally, but a lack of stimulation in the form of physical activity and media can cause children's fine motor skills to fail. perfectly developed.Methods: This study was a quasi-experimental study with a pre test – post test with control group design, aiming to determine the difference in effectiveness between the combination of brain gymnastics and groove board maze educational games, brain gymnastics alone, and placebo (without intervention) on improving fine motor skills in Aisyiyah Bustanul Athfal Kindergarten, Malimongan Tua branch, Makassar city, carried out at Aisyiyah Bustanul Athfal Kindergarten, Malimongan Tua Branch, Makassar City, with a sample of 30 children who experienced delays in fine motor development according to inclusion criteria, divided according to randomized into 3 groups: the treatment group was given brain gymnastics and educational maze board game tools, the control group was given brain exercises, and the placebo group (without intervention).Results: Based on the Wilcoxon test analysis, p <0.05 was obtained in 3 sample groups, which means that the three sample groups produced a significant increase in fine motor skills. Based on the results of the One Away Anova test, a p value <0.05 was obtained, which means that there was a significant difference between the combination of brain gymnastics and the groove board maze educational game tool, brain exercise alone, and without intervention on improving fine motor skills in kindergarten children.Conclusion: the combination of brain gymnastics and the groove board maze educational game tool is most effective than brain gymnastics alone and without intervention in improving fine motor skills in Aisyiyah Bustanul Athfal Ranting Malimongan Tua Kindergarten children.Keywords: Brain gym, educational game tool maze groove board, fine motor skills, preschool age children